2020
DOI: 10.2174/1381612826666200408101550
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Anti-Inflammation Effects of Flavonoids in Chronic Inflammatory Diseases

Abstract: Background: Inflammation is a complex response of the host defense system to different internal and external stimuli. It is believed that persistent inflammation may lead to chronic inflammatory diseases such as, inflammatory bowel disease, neurological and cardiovascular diseases. Oxidative stress is the main factor responsible for the augmentation of inflammation via various molecular pathways. Therefore, alleviating oxidative stress is effective a therapeutic opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 112 publications
1
13
0
Order By: Relevance
“…Terpene trilactones and flavonoids are the most important active components in GBDP. It has been reported that flavonoids have strong anti-inflammatory, antioxidative, and anti-apoptotic effects, which may have potential protective effects against liver I/R injury [40][41][42]. Moreover, as the unique active components of GBDP, ginkgolides and bilobalide have been found to exhibit an antagonistic effect on PAF receptor specifically, which is deemed to associate with the protective effect in I/R injury [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Terpene trilactones and flavonoids are the most important active components in GBDP. It has been reported that flavonoids have strong anti-inflammatory, antioxidative, and anti-apoptotic effects, which may have potential protective effects against liver I/R injury [40][41][42]. Moreover, as the unique active components of GBDP, ginkgolides and bilobalide have been found to exhibit an antagonistic effect on PAF receptor specifically, which is deemed to associate with the protective effect in I/R injury [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Terpene trilactones and avonoids are the most important active components in GBDP. It has been reported that avonoids have strong anti-in ammatory, antioxidative, and anti-apoptotic effects, which may have potential protective effects against liver I/R injury [40][41][42]. Moreover, as the unique active components of GBDP, ginkgolides and bilobalide have been found to exhibit an antagonistic effect on PAF receptor speci cally, which is deemed to associate with the protective effect in I/R injury [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are not only the most important plant pigments, but also chemical messengers, physiological regulators and cell cycle inhibitors [ 49 ]. For humans, these compounds have been demonstrated to have a variety of biological and pharmacological effects, including antimicrobial, antihypertensive, antioxidant, antiaging, antifatigue and anti-inflammatory activities as well as liver protection, immune enhancement, radiation protection and lipid profile improvement functions [ 50 , 51 , 52 , 53 ].…”
Section: Anticancer Effects Of Astragalus and Its Main Medicative Compounds/extractsmentioning
confidence: 99%